Samarium(II) iodide-promoted reactions of 2,3-epoxycycloalkanone hydrazones - Kang, HY; Hong, WS; Lee, SH; Choi, KI; Koh, HY (GEORG THIEME VERLAG, 1997)
The reaction of hydrazones of 2,3-epoxycycloalkanone promoted by samarium(II) iodide has been investigated to study the behavior of the compounds containing C=N bonds in the presence of this powerful single-electron transfer reagent. For the hydrazones derived from 2,3-epoxycyclopentanone and 2,3-epoxycyclohexanone, 3-iodo-2-cycloalkenols were isolated while the corresponding 2-cycloalkenols were the products when the hydrazones from 2,3-epoxycycloheptanone and 2,3-epoxycyclooctanone were reacted.
Keywords: ORGANIC-SYNTHESIS; LANTHANIDES; CYCLIZATION; RADICALS; IMINES